The Disappearing Winter: The Diminishing of Seasonal Variations in the Circulation of News. The Case of Sweden 1790 to 1829 - Johan Jarlbrink; Patrik Lundell (Tijdschrift voor Mediageschiedenis, 2025)
Seasonal and maritime-related variations in newspaper content and circulation speed have been observed in the literature. This study of Swedish conditions 1790–1829 documents such differences. However, its focus is on domestic circulation and its dependence upon, among other things, incoming foreign news. By combining a computer-assisted method that tracks text reuse with close readings, and by breaking down the circulation into genres and categories of duration, historical change in these variations is made visible. While previous research has emphasised the explanatory power of technology, this article shows that more factors must be considered. Although technological infrastructural advancements were very limited, circulation times decreased and seasonal variations were evened out. This is best explained, this article suggests, by the growth of the system itself, by overall policy changes and by the increased scope for individual actors to change the culture and the protocols of the system, whether intentionally or not.